Front Cover: Interference in Atomic Magnetometry (Adv. Quantum Technol. 12/2020). Issue 12 (14th December 2020) - Jiang, Min; Xu, Wenjie; Li, Qing; Wu, Ze; Suter, Dieter; Peng, Xinhua
Abstract : A novel interference effect in atomic magnetometers is uncovered and characterized, which introduces an important systematic error to greatly deteriorate the accuracy of magnetic‐field measurements (see article number 2000078 by Xinhua Peng and co‐workers). Such an effect provides a first explanation for the phenomenon of asymmetric spectra observed in ultra‐low‐field nuclear magnetic resonance. It is anticipated that the magnetic interference phenomena uncovered here will stimulate interesting new researches in a wide range of magnetometers and their applications in biological, physical, and chemical science.